Design of microplasma electrodes for plasma-on-chip devices - Chang, Chun-Yao; Sasaki, Minoru; Kumagai, Shinya; Wang, Gou-Jen (Journal of Physics D: Applied Physics, 2016)
Plasma-on-chip (POC) devices have been developed to achieve plasma treatment of individual cells. However, the microcathode of a POC can be easily damaged during plasma firing. In this study, microplasma electrodes for POC devices were designed to enhance the lifetime of plasma electrodes while maintaining their microplasma characteristics. An electrode comprising a 20 nm-thick titanium layer and a 200 nm-thick gold layer on a silicon substrate was fabricated by photolithography and evaporation. Experimental results illustrated that a microelectrode with a blunt-ended cathode and a flat anode can extend the firing lifetime by as much as 30 times that of a double-tip electrode. We also fabricated a 220 nm-thick pure titanium electrode to further extend the lifetime of the electrode. Experimental results showed that the pure titanium electrode can further extend the lifetime 60 fold when compared with an Au / Ti hybrid electrode. However, the voltage requirement for the pure titanium electrode is only 20 V higher than that for the Au/Ti electrode. The pure titanium microelectrode proposed in this study possesses several advantages such as low cost, simple fabrication, and high biocompatibility. Hence, it is highly feasible for POC applications.